Pengembangan LKS Biologi Berbasis Inquiry Terbimbing Materi Keanekaragaman Hayati Siswa Kelas XI SMAN 7 Soppeng - Ruhena; Muhammad basriadi; Novita darti; Andi Badli Rompegading (LPPM Universitas Puangrimaggalatung, 2021)
The development of LKS based on guided inquiry on the material of biodiversity in class XII SMA. This type of research is research and development which refers to the development of a 4D model, namely the process of conducting an initial investigation then designing then validating and revising the results as well as conducting socialization so that a learning tool can be obtained that can be used as a guide in implementing appropriate learning. done by students.